THE RELATIONSHIP BETWEEN MOTHER'S CHARACTERISTICS AND FAMILY INCOME WITH THE INCIDENT OF STUNTING IN CHILDREN IN PESISIR SELATAN REGENCY - Putri Nelly Syofiah; Gina Muthia; Eka Putri Primasari; Alwiyah Rahmi; Lulu Shabina Suyitno; Safira Sucia Nurjanah; Savira Salsabila (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Stunting remains a major public health issue in Pesisir Selatan Regency, where the prevalence reached 29.8% in 2023, affecting children’s physical growth and cognitive development. This study aimed to analyze the association between maternal characteristics (parity, maternal age during pregnancy, age at marriage, birth spacing, education level, occupation, and exclusive breastfeeding) and family income with stunting among children under five. A cross-sectional design was employed involving 30 mothers of young children selected from the working area of Kayu Gadang Public Health Center. Data were collected using structured questionnaires and anthropometric measurements, and analyzed using the Chi-Square test.The results showed that 66.7% of the children were stunted. Maternal characteristics—including parity, maternal age during pregnancy, age at marriage, birth spacing, educational level, and occupation—were not significantly associated with stunting (p>0.05). Significant associations were found between exclusive breastfeeding (p=0.019) and family income (p=0.026) with stunting. Children from families earning below the regional minimum wage and those not exclusively breastfed were more likely to be stunted.In conclusion, exclusive breastfeeding and family income are significant predictors of stunting. Therefore, interventions should emphasize improving exclusive breastfeeding practices and strengthening economic support for at-risk families. These findings are expected to guide evidence-based stunting prevention strategies in Pesisir Selatan Regency.